From Decline to Revival: Policies to Unlock Human Capital and Productivity - Dan Andrews; Balázs Égert; Christine de La Maisonneuve (CESifo GmbH, 2024)
The productivity slowdown in many OECD countries over the last decades coincided with a significant deceleration in human capital growth. We show that nearly one-sixth of this productivity slowdown can be attributed to a decline in human capital growth, mainly driven by the decline in the quality of human capital, as measured by PISA scores. An analytical framework used to understand this decline considers education policies, the until recently largely unregulated use of digital devices in classrooms and the impact of the COVID-19 pandemic. The results highlight the negative effects of smartphone and social media usage on student performance and suggest that responsible internet use programs and education policy reforms could mitigate these effects. The paper also shows that public policies can help countries deploy more efficiently their human capital to enhance productivity. Without policy intervention, continued declines in PISA scores could reduce long-term MFP growth by nearly 3%. Combining education reforms with structural reforms could mitigate these effects and boost long-term MFP by about 1.5%. Therefore, efficient deployment and reallocation of human capital are crucial for sustaining productivity growth.
Keywords: E24; I20; I25; I26; I28; 330; productivity slowdown; human capital; PISA scores; digital device; public policies; OECD